Reduction in the risk of major adverse cardiovascular events with the BET protein inhibitor apabetalone in patients with recent acute coronary syndrome, type 2 diabetes, and moderate to high likelihood of non-alcoholic fatty liver disease - Peter P. Toth; Gregory G. Schwartz; Stephen J. Nicholls; Aziz Khan; Michael Szarek; Henry N. Ginsberg; Jan O. Johansson; Kamyar Kalantar-Zadeh; Ewelina Kulikowski; Ken Lebioda; Norman C.W. Wong; Michael Sweeney; et al. (Elsevier, 2022)
Background: Nonalcoholic fatty liver disease (NAFLD) is common among patients with type 2 diabetes mellitus (T2DM) and is associated with increased risk for coronary atherosclerosis and acute cardiovascular (CV) events. We employed the validated, non-invasive Angulo NAFLD fibrosis score (FS) in an intervention study in patients with T2DM and recent acute coronary syndrome (ACS) to determine the association of FS with CV risk and treatment response to apabetalone. Apabetalone is a novel selective inhibitor of the second bromodomain of bromodomain and extra-terminal (BET) proteins, epigenetic regulators of gene expression. Methods: The Phase 3 BETonMACE trial compared apabetalone with placebo in 2,425 patients with T2DM and recent ACS. In this post hoc analysis, we evaluated the impact of apabetalone therapy on CV risk, defined as a composite of major adverse cardiovascular events (MACE: CV death, non-fatal myocardial infarction [MI], or stroke) and hospitalization for heart failure (HHF) in two patient categories of FS that reflect the likelihood of underlying NAFLD. Patients were initially classified into three mutually exclusive categories according to a baseline Angulo FS <-1.455 (F0-F2), -1.455 to 0.675 (indeterminant), and >0.675 (F3-F4), where F0 through F4 connote fibrosis severity none, mild, moderate, severe, and cirrhosis, respectively. The composite of ischemic MACE and HHF in the placebo group was higher in indeterminant and F3-F4 categories compared to the F0-F2 category (17.2% vs 15.0% vs 9.7%). Therefore, for the present analysis, the former two categories were combined into an elevated NAFLD CVD risk group (FS+) that was compared with the F0-F2 group (lower NAFLD risk, FS0-2). Results: In 73.7% of patients, FS was elevated and consistent with a moderate-to-high likelihood of advanced liver fibrosis (FS+); 26.3% of patients had a lower FS (FS0-2). In the placebo group, FS+ patients had a higher incidence of ischemic MACE and HHF (15.4%) than FS0-2 patients (9.7%). In FS+ patients, addition of apabetalone to standard of care treatment lowered the rate of ischemic MACE compared with placebo (HR = 0.79; 95% CI 0.60-1.05; p=0.10), HHF (HR = 0.53; 95% CI 0.33-0.86; p=0.01), and the composite of ischemic MACE and HHF (HR = 0.76; 95% CI 0.59-0.98; p=0.03). In contrast, there was no apparent benefit of apabetalone in FS0-2 patients (HR 1.24; 95% CI 0.75-2.07; p=0.40; HR 1.12; 95% CI 0.30-4.14; p=0.87; and HR 1.13; 95% CI 0.69-1.86; p=0.62, respectively). Over a median duration of 26.5 months, FS increased from baseline in both treatment groups, but the increase was smaller in patients assigned to apabetalone than to placebo (p=0.04). Conclusions: Amongst patients with T2DM, recent ACS, and a moderate-to-high likelihood of advanced liver fibrosis, apabetalone was associated with a significantly lower rate of ischemic MACE and HHF and attenuated the increase in hepatic FS over time.